Scientific Controversies and Epistemological Sensitization - Effects of an Intervention on Psychology Students’ Epistemological Beliefs and Argumentation Skills - Klopp, Eric; Stark, Robin (Frontiers in Education, 2022)
The present study investigates the effects of an intervention presenting resolvable, scientific controversies and an epistemological sensitization measure on the changes in psychology students’ epistemological beliefs. Drawing on the notion that the presentation of resolvable scientific controversies induces epistemological doubt and the notion that inducing epistemological doubt is eased in the presence of an epistemological sensitization, we used an epistemological beliefs intervention consisting of five resolvable controversies that were applied in a sample consisting of psychology students. We hypothesized that the intervention would reduce absolutist and multiplist epistemological beliefs while, at the same time, increasing evaluativist beliefs. We also assumed that the epistemological sensitization would enhance the effect of the intervention. For a domain-specific questionnaire, the results indicated a reduction of absolutist epistemological beliefs regardless of the presence of the epistemological sensitization. Unexpectedly, there was a backfire effect indicated by a rise of multiplist beliefs. For a domain- and topic-specific questionnaire, there was no significant reduction of absolutist and multiplist beliefs but a significant increase in evaluativist beliefs when the epistemological sensitization was present. Finally, a measure assessing argumentation skills revealed an increase in argumentation skills only when the epistemological sensitization is present. Finally, we discuss limitations, educational implications, and directions for future research.